Growth of Spirulina spp. at different temperatures and their impact on pigment production, oxidants and antioxidants profile - Maha Rehman; Talha Shah; Talha Shabir; Iqra; Taj Ud Din; Mamata Chahar; Rajni Verma; Damanjeet Aulakh; Muhammad Daud; Rehan Naeem; Abdela Befa Kinki (PLoS ONE, 2025)
The study investigated the effect of different temperatures on the growth, pigment production, oxidative stress markers, and antioxidant profile of Spirulina spp. The results showed that the maximum growth of Spirulina was observed at 20°C, while the chlorophyll a, chlorophyll b, and carotenoid contents decreased at higher temperatures. Additionally, the concentration of oxidants such as MDA and H2O2 increased with temperature, while the concentration of antioxidants such as SOD, POD, and APX also increased with temperature. However, the optimal concentration of antioxidants varied with temperature, with the highest concentration of SOD and POD observed at 30°C and the highest concentration of CAT and APX observed at 20°C. Overall, the study suggests that the growth of Spirulina is temperature-dependent, with optimal growth observed at 20°C. Additionally, the study highlights the complex relationship between temperature and oxidative stress in Spirulina, with both oxidants and antioxidants increasing with temperature. However, the optimal concentration of antioxidants varies with temperature, indicating the need for further research to understand the mechanisms underlying these observations. The findings of this study have implications for the cultivation of Spirulina, particularly in regions where temperatures fluctuate significantly, and may also have implications for the use of Spirulina as a dietary supplement.